Gp350-anchored extracellular vesicles: promising vehicles for delivering therapeutic drugs of B cell malignancies - Huiqing Xiu; Xi Nan; Danfeng Guo; Jiaoli Wang; Jiahui Li; Yanmei Peng; Guirun Xiong; Shibo Wang; Changjun Wang; Gensheng Zhang; Yunshan Yang; Zhijian Cai (Asian Journal of Pharmaceutical Sciences, 2022)
Although chimeric antigen receptor-modified (CAR) T cell therapy has been successfully applied in the treatment of acute B lymphocytic leukemia, its effect on Burkitt lymphoma (BL) and chronic B lymphocytic leukemia (B-CLL) is unsatisfactory. Moreover, fatal side effects greatly impede CAR T cell application. Extracellular vesicles (EVs) are excellent carriers of therapeutic agents. Nevertheless, EVs mainly accumulate in the liver when administered without modification. As an envelope glycoprotein of Epstein–Barr viruses, gp350 can efficiently bind CD21 on B cells. Here, gp350 was directly anchored onto red blood cell EVs (RBC-EVs) via its transmembrane region combined with low-voltage electroporation. The results showed that gp350 could anchor to RBC-EVs with high efficiency and that the resulting gp350-anchored RBC-EVs (RBC-EVs/gp350Etp) exhibited increased targeting to CD21+ BL and B-CLL relative to RBC-EVs. After the loading of doxorubicin or fludarabine, RBC-EVs/gp350Etp had powerful cytotoxicity and therapeutic efficacy on CD21+ BL or B-CLL, respectively. Moreover, RBC-EVs/gp350Etp loaded with a drug did not exhibit any apparent systemic toxicity and specifically induced the apoptosis of tumor B cells but not normal B cells. Therefore, our findings indicate that drug-loaded RBC-EVs/gp350Etp may be adopted in the treatment of CD21+ B cell malignancies.